Exploring And Evaluating The Efficiency And Satisfaction Of E-Book Among Students In Multimedia University - Fen, Ching Pei (2009)
The purpose of this study is to explore the current scenario of e-book usage among Multimedia University students; and to evaluate the efficiency and satisfaction of e-books among the students.